If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4/(v+10)=6/(v+6)
We move all terms to the left:
4/(v+10)-(6/(v+6))=0
Domain of the equation: (v+10)!=0
We move all terms containing v to the left, all other terms to the right
v!=-10
v∈R
Domain of the equation: (v+6))!=0We calculate fractions
v∈R
4v/((v+10)*(v+6)))+(-(6*(v+10))/((v+10)*(v+6)))=0
We calculate terms in parentheses: -(6*(v+10))/((v+10)*(v+6))), so:We add all the numbers together, and all the variables
6*(v+10))/((v+10)*(v+6))
We multiply all the terms by the denominator
6*(v+10))
We multiply parentheses
6v+
We add all the numbers together, and all the variables
6v
Back to the equation:
-(6v)
-6v+4v/((v+10)*(v+6)))+(=0
We multiply all the terms by the denominator
-6v*((v+10)*(v+6)))+(+4v=0
We add all the numbers together, and all the variables
4v-6v*((v+10)*(v+6)))+(=0
| 49-(-2-x)^2=0 | | 42=7/8f | | 3/10.5=10/p | | 1/5x+1/3=5(4/5x-5) | | 0.48x^2-0.2x+1=0 | | x=5x5 | | 3.333333333333333333333333333333333333333*x−5.3=−2 | | 31 3x−5.3=−2 | | -x+3=-2x-18 | | 80=8(n+3) | | 5x+x-24=180 | | 2x-1=1.5-1.5 | | 3x-14+1(x-9)=2x-2 | | 4(-4-2m)=-2(m-2)-2m | | 2|3x+9|=36 | | -1+v/4=3 | | x-6=48-5x | | 20=2t+3t^2 | | 8b-7b=17 | | 2+2.5v=0.55 | | 2(x+12)=x+24-x | | -4=4x+-3 | | 6h+22=46 | | (x)*(x+1)*(2)*(1)*(x+2)=112 | | 4(x-5)-7x=-8 | | (1/2)-3x=(1/2) | | -4=4x+2 | | 8/5a=1/2+a | | 0=160−16t^2 | | 4y-12=y-17 | | 2r+0.3=0.6 | | (x)(x+1)(2)(1)(x+2)=112 |